Penerapan Media Kotak Ajaib untuk Meningkatkan Kemampuan Bahasa Anak di Kelas A RA. Abnaul Amir - Ainung, Nurul; Mania, Sitti; Agusriani, Ade; Kusyairy, Umi; Tayeb, Thamrin (NANAEKE: Indonesian Journal on Early Childhood Education, 2025)
The purpose of this study To determine the process of implementing the magic box media in improving children's language skills in class A Based on the results of the study, the application of the magic box media was carried out clearly and variedly so that it could attract the attention of students by improving language skills. Improvements can be seen from the research that has been conducted in cycles I and II. Students who participate achieve developmental characteristics, students are able to understand the instructions given by the teacher in language that is easy to understand. Improvements in students' language skills can be seen from the child's ability to mention the pictures they get and are able to tell their experiences related to what is remembered. The increase can be seen from the pre-cycle with a percentage of 100% or 15 children have developed (MB) with an average value of 30% which can be said that children have not developed according to the indicator, then in cycle 1 there was an increase with a percentage of 100% or 15 children have developed according to expectations (BSH) and 13 or 2 students who have developed very well (BSB) with an average value of 66% which can be said that students have not developed according to the indicator and continue to cycle II. In cycle II, students experienced a very good increase with a percentage of 100% or 15 students who had developed very well (BSB) with an average value of 98% which can be said to have increased according to the success indicator of 75%, therefore the researcher stopped the Classroom Action research with an average value of 98%.